2014
DOI: 10.4244/eijv9i9a176
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome after implantation of Absorb bioresorbable drug-eluting scaffolds in patients with acute coronary syndromes

Abstract: BVS implantation for patients with ACS is safe, with outcomes comparable with those of drug-eluting metal stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 19 publications
4
47
0
1
Order By: Relevance
“…Recently, bioresorbable vascular scaffolds (BRS) were introduced, which provide temporary vessel scaffolding with drug delivery capacity but do not carry the limitations of a permanent metallic stent in the long term [8,9]. Prospective studies demonstrated BRS safety and efficacy on selected patients [10][11][12], but some studies have reported increased ST rates [13][14][15][16][17][18][19]. However, data on a large sample of ACS patients are still lacking [15,17,[20][21][22][23][24], and only few studies have evaluated the impact of lesion preparation and postdilatation of BRS [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bioresorbable vascular scaffolds (BRS) were introduced, which provide temporary vessel scaffolding with drug delivery capacity but do not carry the limitations of a permanent metallic stent in the long term [8,9]. Prospective studies demonstrated BRS safety and efficacy on selected patients [10][11][12], but some studies have reported increased ST rates [13][14][15][16][17][18][19]. However, data on a large sample of ACS patients are still lacking [15,17,[20][21][22][23][24], and only few studies have evaluated the impact of lesion preparation and postdilatation of BRS [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The ABSORB II trial was the only RCT with published data comparing BVS with DES. 7 Studies conducted by Gori et al and Costopoulos et al included a reference group that was treated with DES 8,9 ; the remaining studies did not include a reference group or report on its outcomes.…”
Section: Included Studiesmentioning
confidence: 99%
“…8,9 Gori et al included only patients with ACS from May 2013 and June 2013 at 1 institution in Mainz, Germany. Treatment allocation was dependent on scaffold availability during implantation and thus was not randomized.…”
Section: Cohort Studiesmentioning
confidence: 99%
See 2 more Smart Citations